MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK MTS DARUL HIKMAH KOTA BIMA - Herman Herman; Nurfathurrahmah Nurfathurrahmah; Irma Rubianti; Bakhtiar Bakhtiar (Jurnal Biotek, 2019)
The aim of this study is to identify the influence of guided inquiry learning model on students' critical thinking skills. The study is conducted by  using quasi-experimental methods with Posttest only control group design. Sample is taken to determine experimental group and control group with purposive technique. A valid and reliable essay instruments were developed based on critical thinking indicators (defining, arguing, withdrawing the conclusions) given to each sample after learning process takes place. Data were analyzed with t-test of significant level α = 0.05. The results show that there is no influence of guided inquiry learning models on students' critical thinking skills. T-test results give counts score is smaller than t test score (0.44 < 2.06).  Based on the observation, there are other factors that also influence on students' critical thinking skills including mental readiness and the effectiveness of students as well as the teacher's skill in facilitating the learning model.